2020
DOI: 10.1029/2019ef001354
|View full text |Cite
|
Sign up to set email alerts
|

China's Trade‐Off Between Economic Benefits and Sulfur Dioxide Emissions in Changing Global Trade

Abstract: China has been suffering from air quality degradation since its ascension into the World Trade Organization in 2001. The unequal exchange that occurs with international trade—that is, developed countries obtaining larger shares of trade‐related value added relative to the shares of trade‐related air pollution incurred locally—may obstruct the greening of global supply chains. In this study, we conduct a multi‐regional input‐output analysis to examine the change in the distribution of economic benefits and sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…Thus, the carbon inequality issue should be analyzed based on a consumption perspective. Based on that, plenty of studies revealed the CO 2 transfer quantity and directions embodied in trade from both national scale and subnational scale. , However, as a key factor in the trade process, the economic gain (value-added) was seldom analyzed accompanied by carbon transfer. , The inequality issue has also been quantitatively measured using multiple approaches. Wang et al constructed an environmental inequality indicator similar to the Pollution Terms of Trade (PTT) to examine the change of economic benefits and sulfur dioxide emissions underlying China’s international trade from 2002 to 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the carbon inequality issue should be analyzed based on a consumption perspective. Based on that, plenty of studies revealed the CO 2 transfer quantity and directions embodied in trade from both national scale and subnational scale. , However, as a key factor in the trade process, the economic gain (value-added) was seldom analyzed accompanied by carbon transfer. , The inequality issue has also been quantitatively measured using multiple approaches. Wang et al constructed an environmental inequality indicator similar to the Pollution Terms of Trade (PTT) to examine the change of economic benefits and sulfur dioxide emissions underlying China’s international trade from 2002 to 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Given the large variations between Chinese regions or sectors, the contributions of drivers to emissions change were evaluated for some specific regions or sectors, such as coal‐fired power plants (Li et al., 2020; Wu et al., 2019), iron and steel industry (Mao et al., 2013), industrial sector (Hang et al., 2019; Liu & Wang, 2017a; W. Zhang et al., 2015), and the three key regions (i.e., the Beijing‐Tianjin‐Hebei region, the Yangtze River Delta region, and the Pearl River Delta region) where Air Pollution and Control Action Plan promulgated in 2013 focused on (Q. Zhang et al., 2019). Recognizing the emission reduction potential from a consumption perspective, some studies also focus on the air pollution emissions transfer (Huo et al., 2014; Li et al., 2019; Liu & Wang, 2015, 2017b; Y. Lu et al., 2019; H. Wang et al., 2017; Yang, Zhang, Fan, Li, & Meng, 2018; Yang, Zhang, Fan, Yu, & Zhao, 2018; H. Y. Zhao et al., 2015), inequity (F. Wang et al., 2020; X. Yang et al., 2019; Zhang, Liu, et al., 2018; Zhang, Wang, et al., 2018), and drivers induced by international and inter‐regional trade (Chen et al., 2020; Guan et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike CO 2 emissions but like SO 2 emissions, waste generation tends to cause environmental issues in the country where it is generated. It would not be surprising if a similar argument could be made with regard to waste as that of Wang et al (2020). There is no doubt that the environmental problems currently facing China are serious.…”
Section: Discussionmentioning
confidence: 96%
“…Even with the inducement to China of final demand exports from China to Japan of 513 billion USD in production value, China's cost to address environmental issues caused by the induced waste generation seems be too much to make this worthwhile. Wang et al (2020) argued that there is a trade-off between economic benefits and sulphur dioxide emissions embodied in global trade, emphasizing the inequality with developed countries. Unlike CO 2 emissions but like SO 2 emissions, waste generation tends to cause environmental issues in the country where it is generated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation